EFEKTIVITAS MEDIA GAMIFIKASI BERBASIS APLIKASI MOBILE UNTUK MENINGKATKAN MINAT BELAJAR BAHASA INDONESIA PADA SISWA SEKOLAH MENENGAH PERTAMA - Maharani Putri Buna; Dhila Fadliah; Ichan Fauzi Rachman (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
Abstract In the rapidly evolving digital era, students are increasingly familiar with mobile devices and digital applications, making a technology-integrated learning approach an urgent necessity. The purpose of this study is to explore the implementation of mobile application-based gamification media in teaching Indonesian language at the junior high school level, and to examine its effectiveness in increasing students’ interest in learning the subject. This study uses a qualitative research method. The results show that the accessibility of mobile devices provides flexibility for students to learn independently and repeatedly. Positive responses from students indicate that gamification media not only aids in understanding the material but also fosters more disciplined and collaborative learning habits.